If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7 + -7a) + 4a = -23 + 3a (7 * -1 + -7a * -1) + 4a = -23 + 3a (-7 + 7a) + 4a = -23 + 3a Combine like terms: 7a + 4a = 11a -7 + 11a = -23 + 3a Solving -7 + 11a = -23 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -7 + 11a + -3a = -23 + 3a + -3a Combine like terms: 11a + -3a = 8a -7 + 8a = -23 + 3a + -3a Combine like terms: 3a + -3a = 0 -7 + 8a = -23 + 0 -7 + 8a = -23 Add '7' to each side of the equation. -7 + 7 + 8a = -23 + 7 Combine like terms: -7 + 7 = 0 0 + 8a = -23 + 7 8a = -23 + 7 Combine like terms: -23 + 7 = -16 8a = -16 Divide each side by '8'. a = -2 Simplifying a = -2
| 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 | | 3x^2+9x-44=0 | | 4(x+6)=21 | | 8(6)+9y=36 | | 12x-4(5+3x)=20 | | c=3+2x | | 5(2c+3d)-8d= | | 2+3x=14+6x | | 2e^3x-8=32 | | 3(6z-1)-5(z+7)=8(z+1) | | -6+3y=-24 | | 9x+18=11x-12 | | 80x^3-60x^2=0 | | 2a^2x^2+x-2a^2b^2x-b^2=0 | | 4x^2-4x^2-x^2+1=0 | | x^2+7x-.75=0 | | 4-3n=8-6n | | -3.25x=15.275 |